Moldy Hazelnut Husk and Shell Related Hypersensitivity Pneumonitis: A Possible Novel Occupational Causative Agent - Kurt, Ozlem Kar; Akanil Fener, Neslihan; Cetinkaya, Erdogan (La Medicina del Lavoro, 2023)
Hypersensitivity pneumonitis (HP) is a complex immune-mediated interstitial lung disease (ILD) triggered by inhalation exposure to environmental or occupational antigens in genetically susceptible individuals. Novel exposure sources and antigens are frequently identified. However, the causative agent remains unidentified in nearly half of HP cases. Early diagnosis for nonfibrotic-HP and quitting the exposure may prevent the disease progression to fibrotic forms and related complications. Here, we present two cases of HP associated with mold exposure in hazelnut husks, leaves, and shells in hazelnut agriculture.